Does pruning affect the structural and ecological productivity of Juniper woodlands in the eastern Hindu Kush? - Din, Nasir Ud; Khan, Nasrullah; Ullah, Rafi; Okla, Mohammad K.; Abdel-Maksoud, Mostafa A.; Saleh, Ibrahim A.; Abu-Harirah, Hashem A.; AlRamadneh, Tareq Nayef (PeerJ, 2025)
Juniperus species play a crucial role in the ecological dynamics of the eastern Hindu Kush region in Pakistan, growing either as mono-specific stands or co-occurring in species-poor communities on mountainous scree slopes, as well as near agricultural and residential areas. Despite their limited population, these trees offer a diverse range of ecosystem services, emphasizing the intricate interdependence between human and natural ecosystems. Given their ecological and commercial importance, local people employ silvicultural practices, such as pruning, to ensure sustainable management. The present study, therefore, aimed to assess conventional pruning practices in the region to understand their impacts on stand structure and ecological productivity. The findings indicated that pruning at an intensity of 30–40% was particularly effective, significantly enhancing dendrometric and reproductive traits, such as height, growth rates, and the production of viable seeds (ANOVA, p < 0.05). Additionally, both diameter at breast height (DBH) and diameter at root collar (DRC) showed positive trends, although the effects were not statistically significant (ANOVA, p > 0.05). Conversely, pruning intensities exceeding 60% exhibited adverse effects on the tree metrics. Our results also highlight the importance of pruning intensities in regulating understory vegetation, soil nutrient dynamics, and the carbon storage capacity of junipers. Notably, moderate pruning demonstrates positive impacts on living carbon biomass (LCB) and on soil organic carbon (SOC) density. In conclusion, adopting moderate-intensity pruning techniques with standard scientific measures could be an effective strategy, not only for improving the structural parameters and carbon budgets amid changing climate conditions but also for ensuring long-term economic advantages in the region.
Keywords: Juniper; Pruning; Dendrometric; Carbon biomass; CO2 sequestration; Hindu Kush mountains